Produksi Bioetanol Dari Nira Nipah Skala 50 Liter Dengan Penambahan Tween 80 Dan Ergosterol Pada Proses Fermentasi Menggunakan Saccharomyces Cerevisiae - Yenti, Silvia Reni; Widodo, Prio; Chairul, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Currently, supply of ethanol was produced globally from sugar and starch. Sugar crops contributed about 61% of total ethanol production while 39% from starch. Nypa sap is one of potential material to be processed to bioethanol. The availability of nypa land is sufficient widely in Indonesia as well as a fairly high sugar content (15-20%) make nypa sap has the potential to be processed into bioethanol as a renewable energy. The aimed of this study was to observe the effect of fermentation time nypa sap with the addition of tween 80 and ergorsterol to bioethanol yield on a scale of 50 liters. Fermentation was carried out in a 70 liter fermenter with a variation of fermentation time about 24, 36, 48, 60, 72, 84, 96 and 108 hours, variations of tween 80 addition about 250 ml and ergosterol as much as 25 grams and without the addition of tween 80 and ergosterol. Effect of addition ergosterol can increase stress tolerance of yeast to osmotic pressure and high bioethanol tolerance in yeast cells. While the effect ofthe addition tween 80 can increase the absorption of ergosterol in plasma membrane and enzymatic accessibility and increasing the level of consumption of glucose in the final stages of fermentation. Fermentation of nypa sap produced the best conditions on the addition of 250 ml tween 80 and ergosterol 25 grams on the fermentation time 96 hours with bioethanol concentration about 16.22% (v /v) or 127.99 mg/mlKeywords: Bioethanol, Ergosterol, Nypa Sap, Saccharomyces Cerevisiae, Tween 80